Kewenangan Badan Penyelesaian Sengketa Konsumen (BPSK) dalam Menyelesaikan Sengketa Asuransi Pasca Keluarnya Peraturan Otoritas Jasa Keuangan (OJK) Nomor 1/POJK.07/2014 - Wisnu Kumala; Yaswirman Yaswirman; Ulfanora Ulfanora (JURNAL MERCATORIA, 2019)
There is a tug of authority in resolving insurance disputes outside the court between the Consumer Dispute Settlement Agency (BPSK) based on Law Nomor 8 of 1999 concerning Consumer Protection with Alternative Dispute Resolution Institutions (LAPS) based on Financial Services Authority Regulation Number 1/POJK.07/2014. This encourages the author to conduct legal research in order to determine the authority of BPSK in resolving insurance disputes as well as the legal consequences of the decision after the issuance of the Financial Services Authority Regulation Number 1/POJK.07/2014 using the statutory approach. This legal research results in the finding that BPSK is still authorized to settle insurance disputes following the issuance of the Financial Services Authority Regulation Number 1/POJK.07/2014, this is based on the provisions of the Lex superior derogat legi inferiori principle. Then there is no legal effect on the BPSK decision after the issuance of the Financial Services Authority Regulation. This is because BPSK's decision has been based on Law Number 8 of 1999 concerning Consumer Protection, whose position is higher than the Regulation of the Financial Services Authority. So there is no need for BPSK to follow the provisions of the regulations whose hierarchy of legislation is lower than the Consumer Protection Act. Therefore BPSK's decision is "final and binding" as explained in Article 54 paragraph 3 of the Consumer Protection Act.